An Observation of the Microstructure of Cervical Mucus in Cows during the Proestrus, Estrus, and Metestrus Stages and the Impact on Sperm Penetration Ability - Fei Huang; Lu-Lu Zhang; Peng Niu; Xiao-Peng Li; Xue-Yan Wang; Jie Wang; Jie-Ru Wang; Jia-Jia Suo; Di Fang; Qing-Hua Gao (Veterinary Sciences)
Cervical mucus not only provides energy for sperm but also forms a barrier to block sperm. This paper aims to study the microstructure of cervical mucus in dairy cows during the proestrus, estrus, and metestrus and its effect on sperm permeability. The experiment collected cervical mucus from 60 Holstein cows during these phases, then observed the different shapes of the mucus after crystallization, classified the mucus, and analyzed its proportions. Scanning electron microscopy was used to observe the ultrastructure of the cervical mucus and measure the micro-pore sizes, followed by sperm permeability tests using mucus from different estrous stages and counting the number of permeated sperm. The results indicate that cervical mucus from cows in different estrous phases includes four types (L, S, P, G), with each type constituting a different proportion. During the proestrus, the L type was significantly more prevalent than the other types (p < 0.05); during estrus, the S type was significantly more prevalent than the other types (p < 0.05); and during the metestrus, the p type was significantly more prevalent than the other types (p < 0.05). The micro-pore sizes of the same type of cervical mucus did not show significant differences across different estrous phases (p > 0.05). However, within the same estrous phase, there were significant differences in the micro-pore sizes among the four types (p < 0.05). The number of sperm that permeated the cervical mucus during estrus and metestrus was significantly higher than during the proestrus (p < 0.05). This study provides data support for the research on cervical mucus in dairy cows.